2017
DOI: 10.1007/978-3-319-65813-1_23
|View full text |Cite
|
Sign up to set email alerts
|

CLEF 2017 NewsREEL Overview: A Stream-Based Recommender Task for Evaluation and Education

Abstract: Abstract. News recommender systems provide users with access to news stories that they find interesting and relevant. As other online, stream-based recommender systems, they face particular challenges, including limited information on users' preferences and also rapidly fluctuating item collections. In addition, technical aspects, such as response time and scalability, must be considered. Both algorithmic and technical considerations shape working requirements for realworld recommender systems in businesses. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…There is limited work on NRS that addresses the temporal dynamics issues. CLEF NewsREEL [12] offered a campaign-style evaluation lab where the goal was to make news recommendation that must respond to a request within a given time frame (100ms). It emphasizes on the timeliness of the news recommendation.…”
Section: Temporal Dynamicsmentioning
confidence: 99%
“…There is limited work on NRS that addresses the temporal dynamics issues. CLEF NewsREEL [12] offered a campaign-style evaluation lab where the goal was to make news recommendation that must respond to a request within a given time frame (100ms). It emphasizes on the timeliness of the news recommendation.…”
Section: Temporal Dynamicsmentioning
confidence: 99%
“…• NewsREEL has been used by practitioners, teachers at universities, and researchers. A survey amongst participants (Lommatzsch et al, 2017) has revealed that one of the main motivations for them to participate was to acquire new skills that are currently in high demand in industry. At the same time, NewsREEL has also been successfully embedded in teaching since students experienced factors associated with working in industry (Hopfgartner et al, 2016).…”
Section: Newsreel Discussionmentioning
confidence: 99%
“…Several authors (Lommatzsch et al (2016); Domann et al ( 2016); Beck et al ( 2017)) have used APACHE SPARK and APACHE MAHOUT. The combinations facilitate periodically building new micro-batches to update the models.…”
Section: The Algorithms Evaluation In the Online Taskmentioning
confidence: 99%
“…The proposed NewsImages dataset has several connections to the NewsREEL dataset [12] originally published in the CLEF NewsREEL challenge. The NewsREEL dataset provides snippets from several German news portals and discussion groups.…”
Section: News Datasetsmentioning
confidence: 99%